2004
DOI: 10.1038/nbt945
|View full text |Cite
|
Sign up to set email alerts
|

An improved cyan fluorescent protein variant useful for FRET

Abstract: Many genetically encoded biosensors use Förster resonance energy transfer (FRET) between fluorescent proteins to report biochemical phenomena in living cells. Most commonly, the enhanced cyan fluorescent protein (ECFP) is used as the donor fluorophore, coupled with one of several yellow fluorescent protein (YFP) variants as the acceptor. ECFP is used despite several spectroscopic disadvantages, namely a low quantum yield, a low extinction coefficient and a fluorescence lifetime that is best fit by a double exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
880
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,000 publications
(915 citation statements)
references
References 20 publications
33
880
1
1
Order By: Relevance
“…To our knowledge, the fluorescent protein variants we generated, in a wild-type GFP backbone, are not commercially available. The GFP and BFP sequences are similar those previously reported (Zernicka-Goetz et al, 1996), and the final CFP we used is similar to a variant called cerulean (Rizzo et al, 2004). An internal EcoRI restriction site present in wild-type DsRed was removed by overlap PCR without altering any codons.…”
Section: Site-directed Mutagenesis and Codon Optimizationsupporting
confidence: 56%
“…To our knowledge, the fluorescent protein variants we generated, in a wild-type GFP backbone, are not commercially available. The GFP and BFP sequences are similar those previously reported (Zernicka-Goetz et al, 1996), and the final CFP we used is similar to a variant called cerulean (Rizzo et al, 2004). An internal EcoRI restriction site present in wild-type DsRed was removed by overlap PCR without altering any codons.…”
Section: Site-directed Mutagenesis and Codon Optimizationsupporting
confidence: 56%
“…One shorter lifetime of 1.1 ns contributing for 33% and one longer lifetime of 3.7 ns contributing for 67% could be recovered. The departure of single-exponential fluorescence decay is also observed by others [18][19][20]. The presence of multiple fluorescent states is most probably due to two different conformations of ECFP in the crystal structure in which two amino acids, Tyr145 and His148, are positioned differently with respect to the fluorophore [21].…”
Section: Fluorescence Decays In Different Water-glycerol Mixturesmentioning
confidence: 70%
“…The interconversion between both conformations is slow on the fluorescence time scale. From site-directed mutagenesis studies, His148 has been found to be the major quencher of the fluorophore [19].…”
Section: Fluorescence Decays In Different Water-glycerol Mixturesmentioning
confidence: 99%
“…In order to get more consistent energy transfer rates, donor species with monoexponential fluorescence decay kinetics should replace ECFP. Candidates may be cerulean with a monoexponential decay paired with yellow fluorescent protein (30), GFP and red fluorescent protein variants (31,32) or YFP paired with mRFP (33). Presently, the fluorescence lifetime s 2 , the effective lifetime s eff , as well as the ratio of amplitudes a 1 /a 2 (describing the contributions of short-lived and long-lived fluorescence) appear to be appropriate parameters for measuring nonradiative energy transfer.…”
Section: Discussionmentioning
confidence: 99%